PERAN PENGUASAAN BAHASA MANDARIN TERHADAP KESIAPAN GENERASI MUDA DALAM PERSAINGAN INTERNASIONAL - Cherish Ardyna; Diananda Afa Nafisa; Fayaza Aulia Safitri; Ruth Kiana Nuratri (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study examines the role of Mandarin language proficiency in preparing Indonesia's younger generation to face international competition as China's global influence increases. A mixed method was used in the study, beginning with a qualitative literature review, followed by a quantitative survey of 38 students in Solo. The results show that 76.3% of respondents are highly interested in learning Mandarin and consider it an important linguistic asset for career opportunities and cross-cultural communication. However, their mastery of vocabulary, basic conversation, and Hanzi writing is still limited. As many as 23.7% of respondents are not interested because they consider the language too difficult and irrelevant. The study concludes that Mandarin proficiency is crucial for the readiness of the younger generation, while recommending the development of a more engaging, relevant, and responsive curriculum and pedagogical approach that addresses motivational barriers and perceptions of difficulty.